If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.38 = 2b + 25(-7) Multiply 25 * -7 0.38 = 2b + -175 Reorder the terms: 0.38 = -175 + 2b Solving 0.38 = -175 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 0.38 + -2b = -175 + 2b + -2b Combine like terms: 2b + -2b = 0 0.38 + -2b = -175 + 0 0.38 + -2b = -175 Add '-0.38' to each side of the equation. 0.38 + -0.38 + -2b = -175 + -0.38 Combine like terms: 0.38 + -0.38 = 0.00 0.00 + -2b = -175 + -0.38 -2b = -175 + -0.38 Combine like terms: -175 + -0.38 = -175.38 -2b = -175.38 Divide each side by '-2'. b = 87.69 Simplifying b = 87.69
| 17x^17=0 | | (Y-3)(Y^2+BY+C)=Y^3-27 | | 19(3-v)+10v=-15 | | -4(6x-7)-3(4+2x)= | | 3x+45=3(x-3) | | 6X(2x-1)= | | 3(2x-y)+6y= | | 0.3(y+4)=0.4(y-2) | | 19=35+9x | | 2(-1)-4-y=12 | | 3y-(y+2x)+x= | | 6y-9-3y+8=0 | | 2(0)-4-y=12 | | 4y-5x=4 | | 2(1)-4-y=12 | | 2z-18-4z=-9 | | -7+u=3 | | y-53=294 | | X^2+6x+6.75=0 | | 4x+7x-3=0 | | -101=w+5.3 | | -0.8k-3.1=.5 | | 4(2x-1)-(3-1)=3 | | 9x^2+18x=22 | | 4(2x-1)-(3x-1)=3 | | x+2/4=27/12 | | F(x)=x*2-6x-15 | | 31=7c+-74 | | 15*15+9*9=x*x | | 4x+206=12+10 | | x-8+9-3=11 | | 6x-5-4x=17 |